Exploration for sediment-hosted copper mineralization in Kaponda Prospect, Central African Copperbelt, Democratic Republic of Congo - Kabunda, Ghislain Mwape (Rhodes University, Faculty of Science, Department of Geology, 2014)
The Kaponda Prospect represents a surface of 915.8 kmÂ² located at about 10 km south of the town of Lubumbashi and 33km NW of Kasumbalesa in the Democratic Republic of Congo (DRC). It lies within Neoproterozoic sedimentary rocks of the Katangan Supergroup in the Central African Copperbelt (CACB). In this province, copper mineralization occurs at different stratigraphic level with different associated alteration. Mineralization is of multistage origin from synsedimentary, diagenetic to post orogenic. Since the discovery of the CACB in the early 20th century, several exploration techniques have been used to delineate Cu deposits. A review and application of these methods including remote sensing, geological mapping, geochemical and geophysical surveys, and drilling, gives an insight of their effectiveness and limitation before analyzing their results from the Kaponda Prospect. The geology and structure of the Prospect is represented by a series of two NW trending disharmonic tight anticlines, locally domal, with cores occupied by either Roan Group or "Grand Conglomerat" Formation. These anticlines are separated by an open syncline made of Kundelungu rocks. Two mains direction of faults are recognized, the NW and NE trending structures. The latter direction are normal transfer faults which can serve as conduit for mineralization. They are related to the late orogenic extension of the Lufilian belt. However NE trending faults are believed to be associated to the climax of Lufilian folding or represents synsedimentary intergrowth faults. Exploration approach for sediment-hosted Cu within Kaponda Prospect, take into account the integration of all information derived from different techniques. Remote sensing is used as aid to geology. Landsat and Google earth images show lineaments that corresponds to lithostratigraphy boundary and domal anticline. Geological mapping identified reduced horizons which can potentially host mineralization, whereas analysis of structure measurements reveals the geometry of fold and direction of its axial plane and hinge. Statistical methods such as the main + 2 standard deviation, the frequency histogram and probability plot, together with experiential method are used to constrain and define Cu and Co thresholds values in soil samples. It appears that in this region, log-probability plot and histogram methods combined with spatial representation and the experience of the region, are the best practice to constrain and separate geochemical background from anomaly data. Ground and airborne magnetic, and radiometric images show specific signatures which map alteration and particularly lithostratigraphy such as "Roan" Group, "Grand Conglomerat" unit, "Nguba" cap carbonates and "Kundelungu" siliciclastic units. Analysis of faults interpreted from geophysical maps identified three major directions: E-W, NE-SW and NW-SE. The E-W faults are also interpreted as normal transfer faults such NE-SW structures, consistent with regional geological map. Although pole-dipole array of induced polarization (IP) survey was directly targeting disseminated Cu sulphide, its results suffer in responding to graphitic rocks and barren pyrite. Only relative small chargeable bodies need to be tested in drilling follow-up. A total of 15 targets have been generated through re-interpretation and integration of both geological mapping and remote sensing, geochemical and geophysical data, as well as existing drilling. Specific recommendations of follow-up works are advised for each type of target.
Keywords: Copper mines and mining -- Central African Copperbelt (Congo and Zambia); Sedimentation -- Central African Copperbelt (Congo and Zambia); Prospecting -- Central African Copperbelt (Congo and Zambia); Geological mapping -- Central African Copperbelt (Congo and Zambia); Geochemistry -- Central African Copperbelt (Congo and Zambia); Induced polarization